2005
DOI: 10.1007/s00234-005-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial lipomas: importance of localization

Abstract: Intracranial lipomas are rare congenital malformations. They are usually pericallosal asymptomatic midline lesions. Other brain malformations are often seen in association with intracranial lipomas. We describe the findings of imaging studies, including computed tomography (CT), magnetic resonance (MR) imaging, and MR angiography, along with a brief review of the literature. The frequency and the spectrum of the associated brain malformations are also discussed. We retrospectively reviewed CT and MR findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
1
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(168 citation statements)
references
References 17 publications
1
150
1
16
Order By: Relevance
“…were larger than those detected in this case series 3,5 . One might speculate that there is a continuum of findings with larger lipomas indicating a more disturbed brain formation explaining the high frequency of associated brain malformations.…”
Section: Resultscontrasting
confidence: 80%
“…were larger than those detected in this case series 3,5 . One might speculate that there is a continuum of findings with larger lipomas indicating a more disturbed brain formation explaining the high frequency of associated brain malformations.…”
Section: Resultscontrasting
confidence: 80%
“…The CT scan demonstrates a marked hypodense nonenhancing lesion in the CPA, with attenuation characteristics similar to adipose tissue (-40 to -100 HU) 1,5,9,10 . Regarding the MR imaging findings, lipomas have signal characteristics similar to the subcutaneous tissue, with high-signal intensity on T1-weighted images, and iso-to hypointense signal on T2-weighted images, usually without contrast enhancement 1 .…”
Section: Casementioning
confidence: 99%
“…The patient signed the informed consent agreeing with the study. diSCuSSion Intracranial lipomas are rare lesions, corresponding to less than 0.1% of all intracranial tumors 3,10,11 . Some authors have suggested that lipomas are congenital malformations because their lack of cellular atypia, dysplasia and other evidences of malignancy, as well as due to the fact that they are usually associated to other malformations 4,7,11 .…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Lipomas make up only 0.1-0.5% of intracranial lesions (14,15). They tend to be placed at the midline, most commonly in the pericallosal cistern (1,6,14).…”
Section: Introductionmentioning
confidence: 99%